Method for improving electric conduction and heat conduction of dummy ingot plate of electroslag furnace in protective atmosphere
By filling conductive filler between the ingot plate and the bottom water tank during the electroslag remelting process, the problems of reduced conductivity and thermal conductivity caused by gaps are solved, and the quality of the ingot and the service life of the equipment are significantly improved.
Patent Information
- Application Number
- CN202411920926.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
During the electroslag remelting process, the gap between the ingot guard plate and the bottom water tank leads to an increase in contact resistance, and a decrease in heat transfer and conductivity, which affects the quality of the ingot and the service life of the equipment.
The gap between the ingot plate and the bottom water tank is filled with conductive filler. The preparation process includes copper powder treatment, ball mill grading, silver plating treatment, mixing and curing to form a filler with excellent electrical and thermal conductivity.
Through the use of filler, the electrical and thermal conductivity between the ingot plate and the bottom water tank is significantly improved, the resistance and thermal resistance are reduced, and the quality of the ingot and the service life of the equipment is improved.
Abstract
Description
Technical Field
[0001] The invention relates to the field of electroslag remelting, and in particular to a method for improving the electrical and thermal conductivity of an ingot starter plate in an electroslag furnace with a protective atmosphere. Background Art
[0002] Electroslag remelting is a metal refining method that uses the resistance heat generated when electric current passes through molten slag to gradually melt the consumable electrode and solidify it into an ingot in a water-cooled crystallizer. During the electroslag remelting process, good heat transfer and electrical conductivity between the ingot guard plate and the bottom water tank are of vital importance to ensure the stability of the remelting process, improve the ingot quality and extend the service life of the equipment.
[0003] At present, in the electroslag remelting process, the ingot guard plate and the bottom water tank are usually in direct contact to achieve heat transfer and electrical conduction. However, due to factors such as manufacturing and installation errors, surface roughness, and thermal deformation during operation, there is often a certain gap between the ingot guard plate and the bottom water tank. These gaps will increase contact resistance and reduce heat transfer and electrical conductivity, thus causing a series of problems.
[0004] For example, the increase in contact resistance makes the current distribution uneven, which can easily lead to local overheating and affect the quality and crystal structure of the ingot. At the same time, the decline in heat transfer performance will lead to poor cooling effect of the bottom water tank, increase the heat load of the equipment, and shorten the service life of the equipment. In addition, uneven heat transfer and conduction may also lead to instability in the electroslag remelting process, increase energy consumption and production costs.
[0005] In order to solve these problems, some measures have been taken in the prior art, such as improving processing accuracy, optimizing installation technology, etc., but these methods are often difficult to completely eliminate the gap, the effect is limited and the cost is high. For example, patent CN201910026942.X sprinkles a layer of powder for improving conductivity between the ingot guide plate and the bottom water tank. This method is too cumbersome to lay. Not only does it require high temperature to smooth the joints, but the gaps in the powder will affect the thermal conductivity and electrical conductivity. Therefore, developing a new technology to effectively improve the heat transfer and electrical conductivity between the ingot guard plate and the bottom water tank has become a technical problem that needs to be solved in the field of electroslag remelting. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for improving the electrical and thermal conductivity of a starter plate in a protective atmosphere electroslag furnace, thereby ensuring the heat transfer and electrical conductivity between the starter plate and a bottom water tank.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for improving the electrical and thermal conductivity of a starter plate of a protective atmosphere electroslag furnace, wherein a conductive filling glue is filled in the gap between the starter plate and a bottom water tank, specifically comprising:
[0009] 1. Preparation of conductive filling glue
[0010] 1) Copper powder treatment: put the copper powder into dilute hydrochloric acid to remove the oxide on the surface of the copper powder;
[0011] 2) ball milling and classification: the copper powder treated in step 1) is ball milled;
[0012] 3) Silver plating treatment: adding the classified copper powder to a mixed solution of formaldehyde and anhydrous ethanol, and then adding a silver ammonia solution to reduce and precipitate silver ions attached to the surface of the powder to prepare silver-plated copper powder;
[0013] 4) Powder drying: Silver-plated copper powder is baked to remove moisture;
[0014] 5) Mixing: adding the silver-plated copper powder and the dried graphite powder into a mixer and mixing them to prepare a conductive mixture;
[0015] 6) Preparation of semi-finished conductive adhesive: add bisphenol A epoxy resin into a three-roll grinder, add the conductive mixture while stirring, add the defoamer after stirring evenly, and make the semi-finished conductive adhesive after stirring thoroughly;
[0016] 7) Curing: The semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for curing to obtain a conductive filling adhesive;
[0017] 2. Installation of starter plate:
[0018] 1) In the preparation stage before electroslag remelting, clean the upper part of the bottom water tank and the lower part of the dummy plate, and then blow dry the surface;
[0019] 2) Apply conductive filling glue evenly on the bottom of the starter plate, place the starter plate on the bottom water tank, and fill the gap between the starter plate and the bottom water tank with conductive filling glue;
[0020] 3) Lay arc starter and pre-melted slag on the upper surface of the ingot starter plate and start the electroslag remelting operation.
[0021] In the step 1) of the step 1, the copper powder is immersed in 5% dilute hydrochloric acid for 20-30 minutes.
[0022] In step 2) of step 1, after ball milling and classification, a powder with a particle size of 3-5 μm is obtained.
[0023] In the step 1, after the powder is classified in step 3), it is added to a mixed solution of formaldehyde and anhydrous ethanol, stirred and reacted at 25° C. for 15-30 minutes, and then a silver ammonia solution with a concentration of 5%-10% is added dropwise, 10 ml of the silver ammonia solution is added to every 1 g of copper powder, stirred and heated to 50-60° C., reacted for 25-35 minutes, and then rinsed with anhydrous ethanol and then rinsed with distilled water until the pH value is 7.0-7.5.
[0024] In step 4) of step 1, the baking temperature of the silver-plated copper powder is 50° C.-65° C.
[0025] In step 5) of step 1, the content of silver-plated copper powder in the electrical mixture is 50%-60%, and the content of graphite is 40%-50%.
[0026] In step 7) of the step 1, the semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for 8-15 minutes for pre-curing, and then the pre-cured semi-finished conductive adhesive is placed in a constant temperature box at 90°C-110°C and kept warm for 5-6 hours for multiple curing to obtain a conductive filling adhesive.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention fills the gap between the starter plate and the bottom water tank with a colloid having conductive properties. The unique adhesion and deformability of the colloid enable the colloid to completely contact the starter plate and the bottom water tank, thereby ensuring heat transfer and electrical conduction.
[0029] The conductive aspect of the present invention: provides good conductivity: copper powder has excellent conductivity, which can significantly improve the conductive performance of the filling glue, so that the current can pass through the contact interface more smoothly, reducing resistance and power loss. Uniform conductive distribution: the filling glue can fully fill the tiny gap between the ingot plate and the bottom water tank, making the current distribution more uniform, avoiding heating and potential damage caused by local current concentration. Forming a stable conductive path: when the filling glue is cured, the copper powders contact each other to form a conductive path, which further enhances the conductive effect, and the surface of the copper powder is silver-plated. Silver has better conductivity than copper. Silver plating on the surface of the copper powder can significantly reduce the contact resistance between the particles, thereby improving the overall conductive performance; copper is easily oxidized in the air to form copper oxide, which will increase resistance and reduce conductive performance. The silver-plated layer can effectively prevent the oxidation of copper and maintain good conductive performance. In electrical equipment that is exposed to air for a long time, the silver-plated copper powder can maintain stable conductivity for a long time. The silver-plated copper powder can conduct electricity more evenly, avoid current concentration in certain parts, and further improve the stability and reliability of conduction.
[0030] The invention has the following aspects in terms of heat conduction: High-efficiency heat transfer: Copper powder and graphite powder have good heat conduction capacity, and can quickly transfer heat from one part of the dummy plate or the bottom water tank to another, which helps to prevent local overheating and maintain its normal working temperature. Reduce interface thermal resistance: The filling glue can effectively reduce the contact thermal resistance between the dummy plate and the bottom water tank interface, ensuring that heat can be efficiently conducted between the two, thereby keeping the equipment within a suitable working temperature range and improving the reliability and service life of the equipment.
[0031] The present invention assists heat dissipation: the filling glue helps to quickly dissipate the heat generated by the starter plate or the bottom water tank during operation, thereby preventing the equipment from being degraded or damaged due to heat accumulation.
[0032] Compared with the existing conductive powder, there is no gap, which improves the heat transfer and conductivity between the starter plate and the bottom water tank. DETAILED DESCRIPTION
[0033] It should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit the present application. The reference to "embodiment" in this article means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] A method for improving the electrical and thermal conductivity of a starter plate of a protective atmosphere electroslag furnace, wherein a conductive filling glue is filled in the gap between the starter plate and a bottom water tank, specifically comprising:
[0035] 1. Preparation of conductive filling glue
[0036] 1) Copper powder treatment: put the copper powder into dilute hydrochloric acid to remove the oxide on the surface of the copper powder;
[0037] 2) Ball milling and classification: The copper powder treated in step 1) is put into a ball mill for ball milling;
[0038] 3) Silver plating treatment: adding the classified powder into a mixed solution of formaldehyde and anhydrous ethanol, and then adding a silver ammonia solution to reduce and precipitate silver ions on the powder surface to prepare silver-plated copper powder;
[0039] 4) Powder drying: Silver-plated copper powder is baked to remove moisture;
[0040] 5) Mixing: adding the silver-plated copper powder and the dried graphite powder into a mixer and mixing them to prepare a conductive mixture;
[0041] 6) Preparation of semi-finished conductive adhesive: add bisphenol A epoxy resin into a three-roll grinder, add the conductive mixture while stirring, add the defoamer after stirring evenly, and make the semi-finished conductive adhesive after stirring thoroughly;
[0042] 7) Curing: The semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for curing to obtain a conductive filling adhesive;
[0043] 2. Installation of starter plate:
[0044] 1) In the preparation stage before electroslag remelting, clean the upper part of the bottom water tank and the lower part of the dummy plate, and then blow dry the surface;
[0045] 2) Apply conductive filling glue evenly on the bottom of the starter plate, place the starter plate on the bottom water tank, and fill the gap between the starter plate and the bottom water tank with conductive filling glue;
[0046] 3) Lay arc starter and pre-melted slag on the upper surface of the ingot starter plate and start the electroslag remelting operation.
[0047] In the step 1) of the step 1, the copper powder is immersed in 5% dilute hydrochloric acid for 20-30 minutes.
[0048] In step 2) of step 1, after ball milling and classification, a powder with a particle size of 3-5 μm is obtained.
[0049] In the step 1, after the powder is classified in step 3), it is added to a mixed solution of formaldehyde and anhydrous ethanol, stirred and reacted at 25° C. for 15-30 minutes, and then a silver ammonia solution with a concentration of 5%-10% is added dropwise, 10 ml of the silver ammonia solution is added to every 1 g of copper powder, and the mixture is heated to 50° C. while stirring and reacting for 25-35 minutes, and then rinsed with anhydrous ethanol and then rinsed with distilled water until the pH value is 7.0-7.5.
[0050] In step 4) of step 1, the baking temperature of the silver-plated copper powder is 50° C.-65° C.
[0051] In step 5) of step 1, the content of silver-plated copper powder in the electrical mixture is 50%-60%, and the content of graphite is 40%-50%.
[0052] In step 7) of the step 1, the semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for 8-15 minutes for pre-curing, and then the pre-cured semi-finished conductive adhesive is placed in a constant temperature box at 90°C-110°C and kept warm for 5-6 hours for multiple curing to obtain a conductive filling adhesive.
[0053] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0054] Example
[0055] A method for improving the electrical and thermal conductivity of a starter plate of a protective atmosphere electroslag furnace, wherein a conductive filling glue is filled in the gap between the starter plate and a bottom water tank, specifically comprising:
[0056] 1. Preparation of conductive filling glue
[0057] 1) Copper powder treatment: 500 g of copper powder was placed in 1 L of 5% dilute hydrochloric acid, stirred and soaked for 20 minutes, then taken out and rinsed with distilled water to remove oxides on the surface of the copper powder.
[0058] 2) Ball milling and classification: The treated copper powder is put into a ball mill and ball milled for 2 hours to obtain a powder with a particle size of 3-5 μm.
[0059] 3) Silver-plating treatment: the ball-milled powder was added to a mixed solution of 800 ml formaldehyde and 200 ml anhydrous ethanol, stirred and reacted at 25 ° C for 15 minutes to make a reducing solution, 5 L of 5% silver ammonia solution was dropwise added to the reducing solution while heating to 50 ° C while stirring and reacting for 25 minutes to reduce the silver ions and precipitate them on the copper powder surface. After the reaction was completed, it was rinsed with anhydrous ethanol 3 times and then rinsed with distilled water until the pH was 7.2 to obtain 525 g of silver-plated copper powder.
[0060] 4) Powder drying: Place the silver-plated copper powder in a vacuum drying oven and dry it at 55°C for 45 minutes.
[0061] 5) Mixing: 400 g of graphite powder (with a particle size of 3-5 μm) dried at 85° C. and silver-plated copper powder were added to a mixer in sequence, and stirred and mixed at a speed of 800 r / min for 30 minutes to prepare a conductive mixture.
[0062] 6) Preparation of semi-finished conductive adhesive: Add 800g of bisphenol A epoxy resin into a three-roll mill, stir at a speed of 100r / min, slowly add the conductive mixture while stirring, and stir for 2 hours. After stirring evenly, add 50g of polyether modified silicone defoamer, continue stirring for 1 hour, and make a semi-finished conductive adhesive after sufficient stirring.
[0063] 7) Curing into glue: The semi-finished conductive glue is placed at room temperature and irradiated with a UV lamp for pre-curing for 8 minutes. The pre-cured semi-finished conductive glue is then placed in a constant temperature box at 90° C. and kept warm for 5 hours for secondary curing to obtain the conductive glue.
[0064] 8) Vacuum packaging.
[0065] 2. Installation of starter plate and electroslag remelting operation
[0066] 1) Preparation of the dummy plate: Grind and clean the bottom of the dummy plate to remove rust and impurities on the surface.
[0067] 2) Bottom water tank treatment: Perform the same grinding and cleaning operations on the upper part of the bottom water tank to ensure that the surface is flat and clean.
[0068] 3) Applying filling glue: Use a scraper to evenly apply the prepared conductive filling glue on the bottom of the cleaned ingot plate. The thickness of the conductive filling glue layer is controlled at 5 mm.
[0069] 4) Install the starter plate: Place the starter plate coated with conductive filling glue on the bottom water tank to ensure accurate positioning. Rely on the gravity of the starter plate to compact the conductive filling glue so that it fully fills the gap between the starter plate and the bottom water tank.
[0070] 5) Laying materials: Evenly lay arc starter and pre-melted slag on the surface of the ingot starter plate.
[0071] 6) Start the electroslag remelting equipment and operate according to normal process parameters.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and basic spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for improving the electrical and thermal conductivity of a starter plate of a protective atmosphere electroslag furnace, characterized in that: Fill the gap between the starter plate and the bottom water tank with conductive filling glue, including:
1. Preparation of conductive filling glue 1) Copper powder treatment: put the copper powder into dilute hydrochloric acid to remove the oxide on the surface of the copper powder; 2) ball milling and classification: the copper powder treated in step 1) is ball milled; 3) Silver plating treatment: adding the classified copper powder to a mixed solution of formaldehyde and anhydrous ethanol, and then adding a silver ammonia solution to reduce and precipitate silver ions attached to the surface of the powder to prepare silver-plated copper powder; 4) Powder drying: Silver-plated copper powder is baked to remove moisture; 5) Mixing: adding the silver-plated copper powder and the dried graphite powder into a mixer and mixing them to prepare a conductive mixture; 6) Preparation of semi-finished conductive adhesive: add bisphenol A epoxy resin into a three-roll grinder, add the conductive mixture while stirring, add the defoamer after stirring evenly, and make the semi-finished conductive adhesive after stirring thoroughly; 7) Curing: The semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for curing to obtain a conductive filling adhesive; 2. Installation of starter plate: 1) In the preparation stage before electroslag remelting, clean the upper part of the bottom water tank and the lower part of the dummy plate, and then blow dry the surface; 2) Apply conductive filling glue evenly on the bottom of the starter plate, place the starter plate on the bottom water tank, and fill the gap between the starter plate and the bottom water tank with conductive filling glue; 3) Lay arc starter and pre-melted slag on the upper surface of the ingot starter plate and start the electroslag remelting operation.
2. A method for improving the electrical and thermal conductivity of a starter plate in a protective atmosphere electroslag furnace according to claim 1, characterized in that: In the step 1) of the step 1, the copper powder is immersed in 5% dilute hydrochloric acid for 20-30 minutes.
3. The method for improving the electrical and thermal conductivity of the starter plate of a protective atmosphere electroslag furnace according to claim 1, characterized in that: In step 2) of step 1, after ball milling and classification, a powder with a particle size of 3-5 μm is obtained.
4. The method for improving the electrical and thermal conductivity of the starter plate of a protective atmosphere electroslag furnace according to claim 1, characterized in that: In the step 1, after the powder is classified in step 3), it is added to a mixed solution of formaldehyde and anhydrous ethanol, stirred and reacted at 25° C. for 15-30 minutes, and then a silver ammonia solution with a concentration of 5%-10% is added dropwise, 10 ml of the silver ammonia solution is added to every 1 g of copper powder, stirred and heated to 50-60° C., reacted for 25-35 minutes, and then rinsed with anhydrous ethanol and then rinsed with distilled water until the pH value is 7.0-7.
5.
5. The method for improving the electrical and thermal conductivity of the starter plate of a protective atmosphere electroslag furnace according to claim 1, characterized in that: In step 4) of step 1, the baking temperature of the silver-plated copper powder is 50° C.-65° C.
6. The method for improving the electrical and thermal conductivity of the starter plate of a protective atmosphere electroslag furnace according to claim 1, characterized in that: In step 5) of step 1, the content of silver-plated copper powder in the electrical mixture is 50%-60%, and the content of graphite is 40%-50%.
7. The method for improving the electrical and thermal conductivity of the starter plate of a protective atmosphere electroslag furnace according to claim 1, characterized in that: In step 7) of the step 1, the semi-finished conductive adhesive is placed at room temperature and irradiated with a UV lamp for 8-15 minutes for pre-curing, and then the pre-cured semi-finished conductive adhesive is placed in a constant temperature box at 90°C-110°C and kept warm for 5-6 hours for multiple curing to obtain a conductive filling adhesive.
Citation Information
Patent Citations
Method for improving electrical conductivity and heat conductivity of ingot protection plate in electroslag remelting process
CN109609781A